Pengaruh Kepemimpinan Transformasional dan Motivasi Kerja Terhadap Organizational Citizenship Behaviour (OCB) Melalui Komitmen Organisasional Sebagai Mediator Terhadap Pegawai Kantor Perwakilan Bank Indonesia Cirebon - Agus Umar Akmad; Edy Hartono; Dedi Muhammad Siddiq (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
OCB emerges as a response to positive reciprocal relationships between individuals and organizations. When employees feel treated fairly, appreciated, and supported, they tend to contribute more than formally expected. The formation of OCB is influenced by several factors, such as leadership style, work motivation, and organizational commitment. This research used quantitative explanatory research. The population was all employees of the Cirebon BI Representative Office, and the sample size was 100 employees. Data collection techniques included both in-person and online methods using the Google Forms platform. Data analysis used the SEM-PLS method with SmartPLS (Partial Least Square) software. The results of this study 1) Transformational leadership has a positive and significant effect on the OCB of KPw BI Cirebon employees. 2) Work motivation does not affect the OCB of KPw BI Cirebon employees. 3) Transformational leadership has a positive and significant effect on the organizational commitment of KPw BI Cirebon employees. 4) Work motivation has a positive and significant effect on the organizational commitment of KPw BI Cirebon employees. 5) Organizational commitment has a positive and significant effect on the OCB of KPw BI Cirebon employees. 6) Organizational commitment has a positive and significant effect on the OCB of KPw BI Cirebon employees. 7) Organizational commitment is able to mediate the influence of work motivation on the OCB of KPw BI Cirebon employees.